THE COMPETENCE APPROACH IN TEACHING THE SECOND FOREIGN LANGUAGE AT NON-LINGUISTIC UNIVERSITY - LAZARIEV, Oleh; MOVCHAN, Liudmyla (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2018)
The article deals with the main purpose of teaching the first and the second foreign languages at higher school. It is stated that the development of the ability and readiness of future experts from different specialties to intercultural communication promote to develop professional communicative competence. The article points out the using of different language teaching methods in order to give future specialists an opportunity to enter into European international educational and professional space.